2019
DOI: 10.1002/pat.4534
|View full text |Cite
|
Sign up to set email alerts
|

Influence type of natural rubber on properties of green biodegradable thermoplastic natural rubber based on poly(butylene succinate)

Abstract: Green biodegradable thermoplastic natural rubber (GB‐TPNR) based on simple blend of natural rubber (NR) and poly(butylene succinate) (PBS) was prepared using three NR alternatives: unmodified NR and epoxidized NR with 25‐ or 50‐mol% epoxide (ie, ENR‐25 or ENR‐50). It was found that ENR‐50/PBS blend showed the best compatibility, which resulted in superior mechanical and thermal properties with the highest crystallinity of the PBS phase, on comparing with the ENR‐25/PBS and NR/PBS blends. This might be attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…High rubber content tended to produce inferior strength of the samples. It can be seen from Figure 6 that ENR-50 blends can withstand loading better than STR5L blends, and this agrees well with previous work [ 23 ]. This was evidently supported by the results from SEM micrographs showing that there was a serious lack of the continuous rigid phase of PCL with incorporation of soft rubber.…”
Section: Resultssupporting
confidence: 91%
“…High rubber content tended to produce inferior strength of the samples. It can be seen from Figure 6 that ENR-50 blends can withstand loading better than STR5L blends, and this agrees well with previous work [ 23 ]. This was evidently supported by the results from SEM micrographs showing that there was a serious lack of the continuous rigid phase of PCL with incorporation of soft rubber.…”
Section: Resultssupporting
confidence: 91%
“…Considering the points made so far, it is very important to raise the awareness of polymer-based materials as being considered the most attractive and commonly used material. In high-waste generating processes, it is however an environmentally concerning class of materials used globally; as it has lowcost and lightweight characteristics [47] [48]. Furthermore, the prospect of high or increasing population demand and the reality of increasing government regulations creates concerns that would require sustainable 'material and process developments' for the benefit of the ecosystem, while also meeting the sustainable and functional demands of several industries.…”
Section: Review Focusmentioning
confidence: 99%
“…Hence, there have been many attempts to increase the application of PBS i.e. polymer blends [1][2][3][4] and/or composites [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber (NR) is a bio-based elastomer with high elasticity. There are many research studies in which the toughness of polymeric matrix has been enhanced by natural rubber [1][2][3][4][7][8]. The examples of some studies have reported bioplastics such as poly(lactic acid) [8] and poly(butylene succinate) [1,[2][3]7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation